Rotating scalarized black holes: the role of the coupling - Staykov, Kalin V.; Doneva, Daniela D.; Fernandes, Pedro Goncalo da Silva; Yazadjiev, Stoytcho (Physical review, 2025)
We perform an in-depth analysis of rotating scalarized black holes in scalar-Gauss-Bonnet gravity, where scalarization is induced by the spacetime curvature. Our results show that even for very large spins, the scalar charge can reach values comparable to those in the static limit, meaning it is not significantly suppressed. Consequently, curvature-induced scalarization can lead to nongeneral relativity signatures of similar magnitude in both static and rapidly rotating cases. For certain coupling parameters, these scalarized black hole solutions remain within the regime of validity of the effective field theory, where the theory has well-posed formulations.